1976
DOI: 10.1038/bjc.1976.6
|View full text |Cite
|
Sign up to set email alerts
|

Serum lysozyme as a marker of host resistance. I. Production by macrophages resident in rat sarcomata

Abstract: Summary.-With progressive growth of syngeneic sarcomata in rats there was a rise in serum levels of lysozyme which correlated with their immunogenicity and their macrophage content. By an examination of lymph/blood differences in normal and in tumour bearing rats and of the production of lysozyme by cells obtained from the tumours and maintained in vitro, it is apparent that the macrophages resident in a tumour mass make a massive contribution to the elevation in serum lysozyme concentrations. Tumour cells did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Lysozyme, in the absence of overt granulocyte infiltration (noted histologically) is a constitutive marker for cells of the monocyte-macrophage series, and we interpret the high levels of this enzyme in tumour chamber fluids as reflecting macrophage infiltration. Serum levels of lysozyme in the tumourbearing animals were modestly elevated, as previously described (Currie & Eccles, 1976). In-vitro examination of tumour cells and macrophages indicates that the high levels of arginase in the tumour extracellular fluids are derived from macrophages resident within the tumour.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Lysozyme, in the absence of overt granulocyte infiltration (noted histologically) is a constitutive marker for cells of the monocyte-macrophage series, and we interpret the high levels of this enzyme in tumour chamber fluids as reflecting macrophage infiltration. Serum levels of lysozyme in the tumourbearing animals were modestly elevated, as previously described (Currie & Eccles, 1976). In-vitro examination of tumour cells and macrophages indicates that the high levels of arginase in the tumour extracellular fluids are derived from macrophages resident within the tumour.…”
Section: Discussionsupporting
confidence: 77%
“…Arginase is present in high concentrations (i.e., higher than the surrounding normal tissues) in animnal tumours amul in granulomas (Edlbacher & Merz, 1927). In studies of skin carcinogenesis, Roberts & Frankel (1949) showed that tumours contain more arginase than normal skin.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated changed immunoglobulin levels might point to concommitant bacterial infection in patients with cervical cancer at the tumor site. However serum lysozyme which is considered as a parameter for macrophage activity has been found unchanged and almost in the normal range in all investigated cancer patients [23], Changes of immunoglobulin levels might be also a reaction to viral infection. An association between infection with herpes simplex virus type II and cervical cancer has been demonstrated in epidemiological [24] and immunological studies [25].…”
Section: Discussionmentioning
confidence: 80%
“…One simple approach to achieve this goal is by incorporating lysozyme in RB chitosan adhesive films. Lysozyme concentrations fluctuate largely in the body, from 1 mg/mL (Temel et al, 1991) in tears to 10 g/mL in serum (Currie & Eccles, 1976) and 1 g/mL or lower in cerebrospinal fluid (Mishra, Batra, Ali, Anupurba, & Das, 2003). In our in vivo study, we tested adhesives with the lysozyme concentration found in tears (∼1 mg/mL) to ensure significant depolymerization, remaining nonetheless in physiological limits.…”
Section: Discussionmentioning
confidence: 99%